Avaliação das atividades antioxidante, anticoagulante e antiproliferativa de extratos aquosos de marsdenia megalantha - Oliveira, Ruth Medeiros de (2011)
The species of the genus Marsdenia, Apocynaceae, are widely used in folk medicine of several countries. In Brazil is found several species belonging to this genus. The in vitro antioxidant, anticoagulant and antiproliferative activities were evaluated to aqueous extracts of stalk, leaf and root of Marsdenia megalantha. In the total antioxidant capacity assay (expressed as ascorbic acid equivalents) the stalk extract showed 76.0 mg/g, while leaf and root extracts 141.3 mg/g and 57.0 mg/g, respectively. The stalk and leaf extracts showed chelating activity around 40% at 1.5 mg/mL, while root extract, at the same concentration showed, 17%. Only the leaf extract showed a significant ability in superoxide scavenging (80% at 0.8 mg/mL). Any extract was able in scavenge hydroxyl, as well anticoagulant activity. The antiproliferative activity of the extracts was evaluated against HeLa tumor cell line. The extracts inhibited in a dose-dependent manner the cell growth. However, the leaf extract showed 80% of inhibition at 1.0 mg/mL, while stalk and root extracts inhibited 63% and 30%, respectively. To assess the mechanism of cell death caused by the leaf extract in HeLa, was performed flow cytometry and western blot. The results show that leaf extract induces cell death by apoptosis through an activation caspase-independent pathway. These data indicate that stalk and leaf extracts obtained have potential to be used as antioxidants and anticancer drugs